A gentlewoman's guide to murder - Hamilton, Victoria, 1957- (Midnight Ink, an imprint of Llewellyn Worldwide Ltd., 2019)
"When Sir Henry Claybourne is murdered, young spinster Miss Emmeline St. Germaine--who has a secret hobby of rescuing young girls from predatory nobility at knife point--fears that she will be suspected of the murder and resolves to solve it" --